OPTIC DISC MELANOCYTOMA; A RARE ENTITY - Mughal, Jamaluddin; Javed, Anum; Arshad, Owais; Nasir, Javeria; Chatni, Mohammad Hanif; Usman, Mohammad (Journal of Ayub Medical College Abbottabad, 2020)
A young male presented with complaints of disturbance of vision and floaters for the past five years with best corrected visual acuity of 6/6 in both eyes. Ophthalmic examination of the anterior segment was normal in both eyes. There was a relative afferent papillary defect in the right eye. Fundoscopic examination of the left eye showed a raised, 3-disc diameter (DD) dark brown lesion arising from the optic disc. Ophthalmic investigations were performed including fundus photos, A-scan, B-scan, Auto-fluorescence, OCT, and FFA. Findings were consistent with those of optic disc melanocytoma. The patient is now kept on close three-monthly follow-up. To the best of our knowledge, there are no published reports from Pakistan so far. Keywords: Optic Disc Melanocytoma; Melanocytic Lesion; Choroidal Melanoma